Ticarcillin concentrations in serum, muscle, and fat after a single intravenous injection. - Daschner, F D (1980)
Ticarcillin concentrations in serum, muscle, and fat were determined simultaneously in 23 patients after the intravenous injection of a single dose of 5 g. The mean concentrations of ticarcillin in serum, muscle, and fat were, respectively, 185 microgram/ml, 18 microgram/g, and 32 microgram/g at 1.0 to 1.5 h after the injections, declining to levels of 11 microgram/ml, 2 microgram/g at 6 to 7 h after the injections. There was no significant difference between the serum tissue ratios at these time periods.